Observations and fine-scale model simulations of gravity waves over Davis, East Antarctica (69 S, 78 E) - Alexander, SP; Orr, A; Webster, S; Murphy, DJ (Journal of Geophysical Research: Atmospheres, 2017)
Large vertical velocities were observed throughout the troposphere at Davis, East Antarctica, on 18 February 2014 by a VHF wind-profiling radar. Simulations using the Met Office Unified Model at 2.2, 0.5, and 0.1 km horizontal grid spacing were able to broadly capture the location, timing, and magnitude of the observed velocities, as well as reveal that they are due to small-scale orographic gravity waves resulting from the interaction between the coastal topography and strong easterly winds associated with a synoptic-scale cyclone situated to the north. The simulations indicated that the gravity waves are responsible for (i) temperature fluctuations which coincided with satellite-observed cloud variations in the vicinity of Davis, suggesting that they have a crucial role in the formation of cirrus clouds, and (ii) large vertical momentum fluxes in the troposphere. The waves are prevented from propagating into the stratosphere by the background winds turning from near-surface easterlies to lower stratospheric northerlies. As well as illuminating and quantifying the role that weather systems have in producing orographic gravity waves along the East Antarctic coastline, studies such as this should be exploited to improve the representation of key localized atmospheric processes in global climate models.